Narrative medicine to investigate the quality of life and emotional impact of inherited retinal disorders through the perspectives of patients, caregivers and clinicians: an Italian multicentre project. Issue 9 (19th September 2022) - Simonelli, Francesca; Sodi, Andrea; Falsini, Benedetto; Bacci, Giacomo; Iarossi, Giancarlo; Di Iorio, Valentina; Giorgio, Dario; Placidi, Giorgio; Andrao, Assia; Reale, Luigi; Fiorencis, Alessandra; Aoun, Manar
Abstract : Objectives: Although inherited retinal disorders (IRDs) related to the gene encoding the retinal pigment epithelium 65kD protein (RPE65) significantly impact the vision-related quality of life (VRQoL), their emotional and social aspects remain poorly investigated in Italy. Narrative Medicine (NM) reveals the more intimate aspects of the illness experience, providing insights into clinical practice. Design and setting: This NM project was conducted in Italy between July and December 2020 and involved five eye clinics specialised in IRDs. Illness plots and parallel charts, together with a sociodemographic survey, were collected through the project's website; remote in-depth interviews were also conducted. Narratives and interviews were analysed through NVivo software and interpretive coding. Participants: 3 paediatric and 5 adult patients and eight caregivers participated in the project; 11 retinologists globally wrote 27 parallel charts; 5 professionals from hospital-based multidisciplinary teams and one patient association member were interviewed. Results: Findings confirmed that RPE65-related IRDs impact VRQoL in terms of activities and mobility limitations. The emotional aspects emerged as crucial in the clinical encounter and as informative on IRD management challenges and real-life experiences, while psychological support was addressed as critical from clinical diagnosis throughout the care pathway for both patients and caregivers; the need for an IRDs 'culture' emerged to acknowledge these conditions, and therefore, promoting diversity within society. Conclusions: The project was the first effort to investigate the impact of RPE65-related IRDs on the illness experience through NM, concomitantly addressing the perspectives of paediatric and adult patients, caregivers and healthcare professionals and provided preliminary insights for the knowledge of RPE65-related IRDs and the clinical practice.